Severe epistaxis and pregnancy ’’about two cases’’ and review of the literature - Baba, Sacko Hamidou; Dicko, Bagayoko Hawa; Dicko, Abdoul Razak; Aminata, Kodio (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Epistaxis is a health ENT problem which is still current, this is one of the commonly encountered emergencies in Rhinology. The nasal mucosa suffered influence systemic, local, metabolic or hormonal disorders causing a slowdown of muco-ciliary function during pregnancy. These observations relate the clinical and therapeutic particularities of the management for severe epistaxis in women during the last trimester of pregnancy. The woman’s hormonal system is unique in its kind due to cyclic changes during pregnancy, the menstrual cycle and menopause. Our clinical observations confirm the effects of these metabolic, endocrinological and physiological alterations related to pregnancy. In a tropical environment with the inadequacy of ENT specialists, base medical personnel is often confronted with delicate clinical situations in the evolution of ENT diseases. Management for epistaxis during pregnancy is special because of its context, well evident diagnosis requires vital gestures as evidenced by our observations. The ear, nose and throat specialist must necessarily be well warned of its physiological changes during pregnancy to better understand the clinical evolution of certain common throat diseases as epistaxis. Epistaxis during pregnancy is a subject that remains topical in the field of care, it is promoted directly or indirectly by hormonal changes. Multidisciplinary management in coordination must be done in a timely manner because the risks are not negligible for the health of the mother and the child.